Development of controlled release systems of biocides for the conservation of cultural heritage - (:unkn) unknown (ELSEVIER SCI LTD, 2017)
The presence of microorganisms is one of the main causes of monument deterioration. Biocides are usually applied after or before restoration in order to prevent or slow down microbial growth. Frequent applications are necessary leading to increased costs and high risks to humans and the environment. The aim of this study is the design of novel controlled release systems comprising a biocide loaded into a mesoporous silica. Pristine MCM41 as well as MCM41 functionalised with carboxy- (MCM41-COOH) and amino-groups (MCM41-NH2) were used. Biotin T and New Des 50, two commercial formulations, were chosen as biocides. The biocide encapsulation was performed adding the mesoporous silica to an aqueous biocide solution. The release of the biocides in water was investigated by UV-Visible Spectroscopy. A further characterisation of the systems was performed to evaluate their structure and features and to speculate about the mechanisms involved in the release. The effect of both surface modifications on the release of biocides, as well as the biological activity of the systems were tested. The high-performing system was applied on a stone specimen from a fountain in Diamantina (Minas-Gerais, Brazil) to assess the effect on the microbial community up to 12 months. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Controlled release; Mesoporous; Biocides; Physical and chemical interactions; Preventive treatment; MESOPOROUS SILICA NANOPARTICLES; ESCHERICHIA-COLI; MCM-41; ADSORPTION; PT(II)